Efforts to Prevent Recurrence of Stroke in Stroke Patients - Junaidi, Junaidi Junaidi; Widiyawati, Wiwik; Suminar, Ervi; Widiharti, Widiharti (INNOVATION RESEARCH JOURNAL, 2024)
Stroke is a major health problem for modern society today. A person who has had a stroke has a greater tendency to have a recurrence of stroke. This study aims to analyze efforts to prevent the occurrence of recurrent stroke in stroke patients at the Neurological Poly of Muhammdiyah Gresik Hospital. This type of research is correlational analysis, which is looking for a relationship between two variables, with a cross sectional approach between independent and dependent variables. The population in this study is all stroke patients at the Neurological Poly. The sample was taken by purposive sampling technique obtained by 48 respondents. The test results showed that the significance of the overall count results was less than 0.05 which meant that there was a significant relationship between prevention efforts, namely blood pressure control, bloodsugar control, obesity, medication adherence, family support and stress to the occurrence of recurrent strokes. Based on the results of the study, it is hoped that health workers can make efforts to prevent recurrent stroke as an important step in handling stroke patients and provide education about it to patients and their families. The hospital should make standard operational procedures or other forms of policies regarding efforts to prevent recurrent strokes. Keywords : Efforts to Prevent Recurrent Stroke, Recurrent Stroke Incidence